2005
DOI: 10.1007/s00213-005-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

The mGluR5 antagonist MPEP selectively inhibits the onset and maintenance of ethanol self-administration in C57BL/6J mice

Abstract: These data indicate that mGlu5 receptors selectively regulate the onset and maintenance of ethanol self-administration in a manner that is consistent with reduction in ethanol's reinforcement function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 73 publications
7
123
0
Order By: Relevance
“…Similarly, the mGluR5 antagonist MTEP also reduces the reinforcing effects of ethanol in rats and mice (Cowen et al, 2005;Cowen et al, 2007). Importantly, these dose-dependent effects of mGluR5 antagonists on ethanol self-administration are not associated with disruptions in motor performance (Besheer et al, 2007b;Cowen et al, 2007;Hodge et al, 2006). By contrast, other recent data indicate that blockade of post-synaptic mGluR1 (also group I) with the highly potent and brain penetrant antagonist JNJ 16259685 reduces alcohol self-administration and progressive ratio performance via nonspecific effects on motor activity in rats (Besheer et al, 2007a, b).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the mGluR5 antagonist MTEP also reduces the reinforcing effects of ethanol in rats and mice (Cowen et al, 2005;Cowen et al, 2007). Importantly, these dose-dependent effects of mGluR5 antagonists on ethanol self-administration are not associated with disruptions in motor performance (Besheer et al, 2007b;Cowen et al, 2007;Hodge et al, 2006). By contrast, other recent data indicate that blockade of post-synaptic mGluR1 (also group I) with the highly potent and brain penetrant antagonist JNJ 16259685 reduces alcohol self-administration and progressive ratio performance via nonspecific effects on motor activity in rats (Besheer et al, 2007a, b).…”
Section: Discussionmentioning
confidence: 97%
“…For example, the non-competitive mGluR5 antagonist MPEP has been shown suppress the reinforcing effects of ethanol in rats and mice (Backstrom et al, 2004;Hodge et al, 2006;Schroeder et al, 2005), attenuate the motivation to self-administer ethanol (Besheer et al, 2007b), block relapse-like behavior in multiple models (Backstrom et al, 2004;Schroeder et al, 2005), and inhibit the discriminative stimulus properties of investigator-and selfadministered ethanol (Besheer et al, 2003;Besheer et al, 2006). Similarly, the mGluR5 antagonist MTEP also reduces the reinforcing effects of ethanol in rats and mice (Cowen et al, 2005;Cowen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the reinforcing effects of ethanol have been successfully demonstrated when the drug is continuously available (Besheer et al, 2004;Hodge et al, 2006;Olive et al, 2000;Risinger et al, 1998Risinger et al, ,1999, data evaluating ethanol reinforcement in mice under a limited access condition is less well studied. Studies with mice responding on a fixed ratio 1 (FR1) (Middaugh et al 2000;Roberts et al 2000) or FR3 (Tsiang and Janak, 2006) reinforcement schedule reported ethanol intake approximating 0.5 g/kg, which correspond to values in rats responding on a FR schedule (e.g., Samson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, little data exist to support the regulation of alcohol-induced changes in NAC neurotransmitter levels by NMDA receptors (Ericson et al, 2003;Gonzales and Roper, 1993) and both mGluR1 and mGluR5 are necessary for the rise in NAC dopamine and glutamate produced by an acute alcohol injection (Lominac et al, 2006). As Group1 mGluR antagonists are effective at blocking various aspects of alcohol reward in rodents (eg Backstrom et al, 2004;Backstrom and Hyytia, 2007;Hodge et al, 2006;Lominac et al, 2006;McMillen et al, 2005;Olive et al, 2005;Schroeder et al, 2005) and can alter sensitivity to the motor effects of alcohol (Lominac et al, 2006), we propose alcohol-induced increases in Group1 mGluR signaling through Homer2 as a key substrate mediating alcohol-induced neurochemical sensitization within the NAC that underlies the development of alcohol-induced behavioral plasticity relevant to alcoholism.…”
Section: Accumbens Homer2b Upregulation Promotes Alcohol Rewardmentioning
confidence: 99%
“…Deletion of Homer2 (Szumlinski et al, 2005b) or pharmacological blockade of either Group1 mGluRs (eg Backstrom et al, 2004;Backstrom and Hyytia, 2007;Hodge et al, 2006;Lominac et al, 2006;Schroeder et al, 2005) or NMDA receptors (eg Boyce-Rustay et al, 2004; for reviews, see Chandler, 2003;Chandler et al, 1998;Hoffman, 2003;Krystal et al, 2003) reduces various aspects of alcohol reward in laboratory animals. Furthering an active and important role for Homer2 proteins in the behavioral effects of alcohol, an intra-NAC infusion of AAV-Homer2b, reverses the alcoholavoiding phenotype of Homer2 KO mice (Szumlinski et al, 2005b).…”
Section: Accumbens Homer2b Upregulation Promotes Alcohol Rewardmentioning
confidence: 99%